Built community: architecture, community, and participation in a permanent supportive housing project. Issue 1 (2nd January 2018) - Huffman, Tim
ABSTRACT: Housing and the social processes that create it are an important part of a better world. The permanent supportive housing movement holds that housing, in addition to a variety of human services, is the most dignified and effective way to help people without homes. But the design of such initiatives matters. This community-based, qualitative research project investigates the connection between space, participation, and community. It draws on the experiences of residents of an innovative housing organization on Skid Row in Los Angeles, California. Residents of the program find community space to be both promising and contested. Their experiences also reveal the way that institutional space can be trauma-informed and impact their overall wellbeing and opportunities for interacting with others. However, their feelings of being a part of the community and their involvement in activities are not always connected, as identity and social context can cause residents to identify or dis-identify with their community despite how involved or uninvolved they are. Intentionally designed community spaces in permanent supportive housing units can respond to trauma and set the stage for interaction, but they cannot solve all problems.